Measurement and prediction of physical properties of aqueous sodium L-prolinate and piperazine as a solvent blend for CO2 removal - Shaikh, M.S. (Institution of Chemical Engineers, 2015)
In this work, physical properties such as density, viscosity and refractive index of aqueous sodium L-prolinate (SP) and piperazine (PZ) as a solvent for CO2 removal were measured at temperatures from 298.15 to 343.15K at 5K intervals. Different mass fractions (w1+w2) of aqueous blends of (SP+PZ) were 0.10+0.02, 0.10+0.05, 0.20+0.02, 0.20+0.05, 0.30+0.02, and 0.30+0.05. It was observed that the density, viscosity and refractive index increase with increasing the mass fraction, and decrease with increasing temperature. The density data were used for theoretical evaluation of thermal expansion coefficients. It was found that thermal expansion coefficient increases slightly with increasing concentration and temperature. Empirical correlations were applied to the measured physical properties in order to calculate the predicted data. The statistical error analysis was carried out, which showed good agreement between experimental and predicted data. Â© 2015 The Institution of Chemical Engineers.